2021
DOI: 10.1177/17411432211009896
|View full text |Cite
|
Sign up to set email alerts
|

Portraits of UK Black and South Asian headteachers five years on: Leadership retention in the age of academization

Abstract: This article analyzes the career trajectories of eight Black and South Asian headteachers who were part of a larger study of three generations of Black, Asian, and Minority Ethnic (BAME) headteachers (28) interviewed in 2015 (Johnson, 2017). Using a longitudinal life history approach and portraiture, it seeks to answer the question, “How do Black and South Asian headteachers narrate their career progression and leadership values over time?” In particular, I explore the growth of academization and the formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The relationship between principals' empathetic leadership and teachers' commitment has received increasing attention in recent education research. Study found that when principals displayed empathy, care, and concern for teachers, it fostered greater teacher commitment, job satisfaction, and retention (Johnson et al, 2021). The researchers attributed this to teachers feeling valued, supported, and invested in by empathetic principals.…”
Section: Introductionmentioning
confidence: 93%
“…The relationship between principals' empathetic leadership and teachers' commitment has received increasing attention in recent education research. Study found that when principals displayed empathy, care, and concern for teachers, it fostered greater teacher commitment, job satisfaction, and retention (Johnson et al, 2021). The researchers attributed this to teachers feeling valued, supported, and invested in by empathetic principals.…”
Section: Introductionmentioning
confidence: 93%